2007
DOI: 10.1007/s11300-007-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Institutional Environment in Transition Economies

Abstract: economic transition, institution, economic growth, foreign direct investment, E6, O4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 27 publications
2
20
1
2
Order By: Relevance
“…His study showed that the decline in production and employment in inefficient domestic firms due to structural reforms in these countries neutralize or even outweigh the positive effect of FDI on economic growth. Contrary to these findings, Kostevc et al (2007) found that FDI can assist in the process of economic growth of transition economies. Variables such as secondary school enrollment as a measure of human capital also had a positive impact on economic growth, albeit not a significant impact, as well as gross-fixed capital accumulation.…”
Section: Effects Of Fdicontrasting
confidence: 68%
See 2 more Smart Citations
“…His study showed that the decline in production and employment in inefficient domestic firms due to structural reforms in these countries neutralize or even outweigh the positive effect of FDI on economic growth. Contrary to these findings, Kostevc et al (2007) found that FDI can assist in the process of economic growth of transition economies. Variables such as secondary school enrollment as a measure of human capital also had a positive impact on economic growth, albeit not a significant impact, as well as gross-fixed capital accumulation.…”
Section: Effects Of Fdicontrasting
confidence: 68%
“…If we were analyzing the FDI in SEECs utilizing the methods employed in for investigations of the effects and determinants in the articles subject to this comparison, the best suited for us would be the methodological approach by Kostevc et al (2007). They succeeded in collecting the most relevant data for examining the effects and determinants of FDI.…”
Section: Suggestions For the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global and country-specific actors (Kostevc et al, 2007) are equally important in determining the long-run movements in equity flows for both Asian and Latin American countries. One study (Globerman and Shapiro, 1999) on Canadian FDI inflow using US and UK GDP for world economic situation, as the two countries are major partners of the Canadian trade, showed statistically insignificant relationship.…”
Section: Global Factorsmentioning
confidence: 99%
“…This process does not include a simple ownership transformation of state enterprises but also the creation of favourable environment for the emergence and development of the private sector. FDI assists in the process of economic growth of these economies since it increases the degree of competition in the domestic market, as well as the efficiency of local companies (Kostovc et al, 2007). This type of capital flow represents opportunity to reduce technological gap between transition and developed countries.…”
Section: Introductionmentioning
confidence: 99%